[PP.33.14] TEI INDEX AS A TOOL FOR THE DIAGNOSIS OF LEFT VENTRICULAR DYSFUNCTION WITH PRESERVED EJECTION FRACTION IN HYPERTENSIVE PATIENTS. (September 2016) - Tissera, G.; Piskorz, D.; Tommasi, A.
Abstract : Objective: The frequency of left ventricular dysfunction (LVD) in patients (p) with hypertension (HBP) and the methodologies used for its detection are controversial issues. The Ventricular Performance Index, known as Tei index, simultaneously evaluates systolic and diastolic function, and could be a useful tool in HBP p with preserved ejection fraction (PEF). To determine the frequency of LVD in HBP p with PEF by Tei Index. Design and method: Case – control study. Patients divided in three groups: 1) HBP p without left ventricular hypertrophy (LVH); 2) HBP with LVH; 3) non-HBP controls. Volumetric >54% was considered PEF. Left ventricular mass index was measured by Devereux method, LVH was considered with values >95 g/m2 in women and >115 g/m2 in men. Transmitral diastolic peak early flow to septal/lateral mitral annulus average peak early diastolic velocities (E/e' ratio). Systolic and diastolic functions were assessed by standard echocardiography and tissue Doppler and measured as the average diastolic excursion rate of the septal and lateral walls at the mitral annulus level in diastole (e' wave) and systole (s wave). Left atrial volume index (LAVI) was measured. 2013 ESH / ESC Hypertension Guidelines cutoff values were considered. Tei index was measured at the lateral and septal walls of the left ventricle in the apical 4-chamber view by tissue Doppler, three measurements of isovolumetric contraction time, ejection time, and isovolumic relaxation time were averaged and a value >0.40 was considered abnormal. Statistical analysis: ANOVA test, p < 0.05 was considered statistically significant. Results: The mean sample age was 57.3+14.5 years, 54.2 % p were males. 88 non LVH HBP p; 19 LVH HBP p; and 11 non-HBP controls were included. Table shows systolic and diastolic left ventricular function results: Figure. No caption available. Conclusions: 1) abnormal left ventricular function is frequent in HBP p, even in the absence of LVH; 2) tissue Doppler obtained Tei Index is a useful tool for the diagnosis of LVD.